Santri, Cigarettes, and Power Relation: Soft Constructivism of Smoking Habit at Pesantren Lirboyo (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2021)
This article aims to directly investigate the phenomenon of smoking in the small santri community within the scope of the Lirboyo Islamic Boarding School in order to get a specific portrait of the santri smoking behavior with the underlying factors. This study was conducted using participant observation techniques to reconstruct the meaning behind the smoking habits of students at the Lirboyo. The relationship pattern between Lirboyo Islamic boarding school and Gudang Garam cigarette company experienced a faint polarization in terms of smoking habit. Tug of the dominance in the social field about the existence of its Islamic unwelcome law against cigarettes running slowly but surely toward the conditions according to the timely demands. The adaptation process regarding the anti-tobacco healthy life outlook was adopted by Lirboyo Islamic Boarding School without reducing the pattern of relations with cigarette producers and consumers. This pattern is called soft-constructivism towards Lirboyo according to the relevant circumstances.